Pengaruh Komitmen, Komunikasi Dan Penanganan Masalah Terhadap Kepercayaan Nasabah Pada Bank Jatim Cabang Banyuwangi - Angga Ade Permana; Muhammad Firdaus; Muhaimin Dimyati (RELASI : JURNAL EKONOMI, 2020)
This study analyzes the effect of commitment, communication, and problem handling on customer trust. The purpose of this study is to test and analyze commitment, communication, and handling problems to customer trust simultaneously or partially. The sampling technique in this study is nonprobability sampling and uses purposive sampling. The sample in this study amountedto 125 sample respondents to customers. The research method used in this study is multiple linear regression, t-test, f test,and the coefficient of determination R2. based on the results of the study indicate that the variables commitment (????1), communication(????2), and problem handling (????3) simultaneously influence the customer's trust and commitment variable (????1) and problem handling (????3) partially effect on customer trust while communication (????2) has no partial effect on customer trust in the East Java bank in Banyuwangi. Keywords:commitment, communication, problem handling,andtrust